Inkjet‐Printed and Deep‐UV‐Annealed YAlOx Dielectrics for High‐Performance IGZO Thin‐Film Transistors on Flexible Substrates. (28th March 2019) - Bolat, Sami; Fuchs, Peter; Knobelspies, Stefan; Temel, Ozgur; Sevilla, Galo Torres; Gilshtein, Evgeniia; Andres, Christian; Shorubalko, Ivan; Liu, Yujing; Tröster, Gerhard; Tiwari, Ayodhya N.; Romanyuk, Yaroslav E.
Abstract: Recent developments in inkjet printing have proven it a viable method for low‐cost and large‐area coating of oxide materials. The main drawback of this method is the common requirement of a post‐deposition annealing (PDA) of the printed layers at relatively high temperatures ( T > 200 °C). This sets a requirement for the substrate to have high glass transition temperature ( T g ). To reduce the PDA temperature, deep‐ultraviolet (DUV) annealing is proposed as an effective method. In this study, yttrium aluminum oxide (YAlO x ) dielectrics are realized for application in flexible electronic devices via inkjet printing and DUV annealing at a temperature of 150 °C. The effect of the Y concentration on the electrical properties of the dielectrics is investigated. An increase in the Y incorporation is found to increase the dielectric constant and decrease the leakage current of the dielectrics. Flexible indium gallium zinc oxide (IGZO) thin‐film transistors with 50 µm channel widths and 7 µm channel lengths employing printed YAlO x dielectrics are fabricated on polyimide substrates with a maximum processing temperature of 150 °C, yielding a maximum gate leakage current of 10 −13 A, a high I ON / I OFF ratio of 10 8, and a field effect mobility of 4.3 cm 2 V −1 s −1 . Abstract : Inkjet‐printed and DUV‐annealed yttrium aluminum oxide dielectrics are investigated for application in flexible electronics. Indium gallium zinc oxide thin‐film transistors employing printed dielectrics are fabricated at 150 °C. An I ON / I OFF ratio of 10 9 and a mobility of 4.3 cm 2 V −1 s −1 along with the a gate leakage seven orders of magnitude lower than the ON current of the transistors are obtained.